Clustering Fuzzy C-Means Pola Dispersi Asap Kebakaran Lahan Gambut di Kabupaten Bengkalis - Hendrawan, Satya Arisena; Satria, Deki (BRITech, Jurnal Ilmiah Ilmu Komputer, Sains dan Teknologi Terapan, 2019)
The case of peat fires has became a serious problem in Indonesia. It?s impact of peatland fires was felt to the public. One technique to prevent the impact of these problems is try to analyze the pattern of the movement direction so that the smoke peatland can be a form of early prevention solutions. HYSPLIT model is one of technique to analyze the pattern of trajectories based on the meteorological conditions in the region. Fuzzy C-Means clustering is used for providing better result than the cluster of other techniques such as k-means. Based on cluster processing using fuzzy c-means formed fom the value of partition entropy of 0.4554 and partition coefficient of 0.7057, from these factors produce 2 clusters. The results that produce 2 clusters which in the first cluster, smoke peatland fires is at an altitude of 15.89 m AGL and second cluster that the smoke from peatland fires is at an altitude of 135.81 m AGL. Than, the smoke haze has moved to Malaysia, of course the smoke haze is dangerous for societies